Assessment of Psychosocial Problems among old Age at Geriatric Homes in Baghdad City - Qassim, WissamJabbar (International Journal of Psychosocial Rehabilitation, 2020)
Abstract:Elderly is a normal development of human and it is the final part of the life span. Aging is approach of time related change that occurs throughout life. It includes all aspects of the organism. It doesn’t necessary occur in an interrelated or concurrent manner, but it does involve physiological, psychological and social variation that interact to influence behaviour and adaptation. Objectives: The study aims to assess the social problems among adults Old age in Geriatric Home, and explore the association between social characteristics and the psychosocial health problems. Methodology: A cross- sectional study in assessment approach in applied in order to obtain the earlier stated objectives. The study was initiated from October 1st t, 2018 to April 30th , 2019. Results: The results of the study show that the most of the study sample were female, mean age is (70) years marital status is divorced, level of education is elementary school graduates (32.0%), monthly income, less than a half reported that their monthly income is insufficient (46.0%), Less than a half reported that they do so because there is no who cares for them (48.0%). Conclusion: The study reveals that there is a strong relation between psychosocial problems and older adult at Geriatric Homes. Recommendation: The study Recommended that education program or Pamphlet or booklet should be designed and distributes for older adult in houses for further information about caring with elders with psychosocial problems.